EXP utilizing the procedural rhetoric of play and games to create a teaching aid for gender sensitivity training - Romero, Fernando Antonio A.
The purpose of this study is to determine how the popular video game Fortnite: Battle Royale affects child player's understandings of gender stereotypes, and if the design of the game is indicative of dominant-make gender ideology. Though Fortnite's genre and theme is one that most readily caters to adult male motivations of competition and destruction, the game attracts both a substantial female player base and a substantial child player base partially due to its unique visual style and diverse character representation. A total of 55 students in the age-range were surveyed to determine a baseline understanding of what children know about gender and Fortnite. Four child players were asked to keep a visual diary to determine how they internalize and interpret their in-game actions. Four child streamers were observed to analyze how they perform both inside and outside of the game. Three teachers and one parent were interviewed to gain their perspective on the game as played by children. A formal analysis and iconography were conducted to analyze trends in the game's design. The study found that Fortnite mostly conforms to and reinforces dominant-male gender ideology due to the traditional and unequal representation in its male and female characters, and due to how domination through violence is the main mechanic and central goal. The game does not challenge a player's pre-existing gender ideologies but rather allows them to utilize and practice it through play. Parents and teachers largely do not comment on or engage with the game, instead accepting it as part of their children's socio-cultural capital. The research concludes on the finding that the game enables children to practice their existing gender ideologies in a context that is influenced by dominant-male gender ideologies. Overall, the game's violent or sexist messages are largely taken-for-granted because of its cartoonish visuals, and because of how the game has become embedded in the social and popular culture of children. To combat this, this project aims to create a game that can be used to teach about gender issues and against gender stereotypes. EXP is a board game intended to be used as a teaching aid in gender sensitivity training. The game is targeted towards families as they are one of the first institutions that play a role in the development of a child's foundational understanding of gender. Utilizing the unique rhetorical capabilities afforded by games and by play, EXP attempts to help its players be introduced to and be more aware of the issues of gender stereotyping and bias in a more empathetic, digestible, and engaging manner. The mode of a board game was chosen for three main reasons: the social nature of playing board games which would allow players to share their experiences, the impactful rhetoric that arises from a player's first-hand interaction with mechanics and systems, and the cheaper cost of production which allows board games to take more risks in their design and messages. In the game, players take the role of adventurers looking for quests to do in the Kingdom of Arcadia in order to get more EXP (experience points). While players have a variety of assets to use in their quests, their adventures are stymied by the increasingly prevalent and outspoken beliefs and biases of the Arcadians. These beliefs limit what players can do or what assets they can use based on the people's restrictive gender stereotypes. The game is intended for groups of 4-10 players, and is suitable for players as young as 10 years old.